2020
DOI: 10.1002/adma.201907247
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Energy Materials

Abstract: Self‐assembly is a bioinspired strategy to craft materials for renewable and clean energy technologies. In plants, the alignment and assembly of the light‐harvesting protein machinery in the green leaf optimize the ability to efficiently convert light from the sun to form chemical bonds. In artificial systems, strategies based on self‐assembly using noncovalent interactions offer the possibility to mimic this functional correlation among molecules to optimize photocatalysis, photovoltaics, and energy storage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 228 publications
(185 reference statements)
0
92
0
Order By: Relevance
“…Self‐assembly of molecules has become a powerful tool for the development of supramolecular nanoscale materials with a myriad of applications in photonics, electronics, and chemical biology among others. [ 1–10 ] In this context, the control over the self‐assembly processes is essential for the development of well‐defined nanostructures with the desired properties and functions. [ 11–18 ] For many years, the design of supramolecular materials has been tackled only considering the equilibrium states of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐assembly of molecules has become a powerful tool for the development of supramolecular nanoscale materials with a myriad of applications in photonics, electronics, and chemical biology among others. [ 1–10 ] In this context, the control over the self‐assembly processes is essential for the development of well‐defined nanostructures with the desired properties and functions. [ 11–18 ] For many years, the design of supramolecular materials has been tackled only considering the equilibrium states of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The full crystallization of macromolecules in synthetic materials is a major challenge, yet many potential functions benefit from crystalline lattices including ferroelectrics, photovoltaics, exciton movement in photocatalysis, and quantum computing in the future, among many others. In this context it has been interesting to find that supramolecular polymers can indeed form highly crystalline structures, while remaining discrete structures that could physically behave as covalent polymers [89] . In 2014 the Stupp laboratory reported on internally crystalline supramolecular polymers that led to enhanced light-harvesting capabilities [ 31 , [55] , [56] , [57] , 68 , [90] , [91] , [92] ].…”
Section: Self-assembled Supramolecular Polymers and Their Hierarchicamentioning
confidence: 99%
“…The π–π interactions among chromophores in these systems drive self-assembly of these molecules in water to form crystalline supramolecular polymers in the presence of electrolytes that screen repulsive electrostatic interactions ( Fig. 4 b-c) [ 31 , 55 , 56 , 68 , [89] , [90] , [91] , 98 , 99 ]. These supramolecular polymers photosensitize reactions by serving as light-harvesting assemblies, and their crystallization improves the size and lifetime of the resulting charge transfer excitons participating in the photocatalysis [31] .…”
Section: Supramolecular Polymers For Energy Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, investigations of the factors governing the formation of structurally defined aggregates of π‐conjugated materials have been pursued vigorously [11,12] . In particular, controlling the formation of specific supramolecular structures has proven important in adjusting the bulk electronic properties [13–20] . Elegant work from several research groups demonstrated the use of tailored supramolecular interactions to achieve this goal, in particular through the use of organogelating systems in which the π‐conjugated components are well‐oriented [1,21–26] .…”
Section: Introductionmentioning
confidence: 99%